Retention of implant retained obturator using two implant placement configurations for maxillectomy cases: in-vitro study - Nourhan I. Aboseada; Faten S. Mohamed; Sonia M. El-shabrawy (BMC, 2024)
Abstract Background Implant-retained obturators for maxillectomy cases have several advantages over traditional obturators but prosthetic design for specific conditions after maxillary resection has several challenges and the appropriate implant placement configuration is essential for improving retention and the stability of the implant-retained obturator. Objectives The present study aimed to assess the retention force of using linear and nonlinear implant placement configurations using ball and socket attachment in implant-retained obturators at the initial retention and after simulation of six months of use. Materials and methods Two identical epoxy resin maxillary models of a completely edentulous unilateral maxillary defect (Brown's class IIb) were used for implant placement, in the first model three implants were arranged with linear placement configuration, and in the second model three implants were arranged in nonlinear placement configuration. For proper sample sizing, 26 models and obturator were used. Two equal groups of obturators (13 for each group) were constructed, each with a different implant placement configuration. Both groups used the same attachment design (a non-splinted ball attachment). Using a cyclic loading machine that served as a dental insertion and removal simulator, each study group was subjected to 500 tension-compression cycles simulating 6 months of use. Using the universal testing machine, each obturator was removed at a speed of 50 mm/min for the crosshead. peak load to dislodgement was measured at the initial retention and after the simulations of six months of use. Data were analyzed using independent and paired t-tests while percent change was analyzed using the Mann Whitney U test. Results There were a statistically significant differences in retention between the nonlinear implant placement configuration for Brown's class IIb maxillectomy and the linear implant placement configuration at initial retention evaluation with p-value of < 0.0001 and after simulation of six months of usage with p-value of < 0.0001 Also, after simulation of 6 months of use group I lose − 24.87 (10.16) % of its retention while group II lose − 17.49 (7.78) %. Conclusions Non-linear implant placement is more retentive at the initial retention and after simulation of six months of use than linear and loses less retention after usage.